PERILAKU PROFESIONAL TENAGA KESEHATAN PADA PELAYANAN KESEHATAN PRIMER PUSKESMAS PELALAWAN KABUPATEN PELALAWAN TAHUN 2013 - Putri, Eka Sri Indra; Afandi, Dedi; Fidiawati, Wiwit Ade (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTProfessional behaviour is an effectuate that is expected of health professionals who provide services to the community including remote areas like in the littoral, one of which coastal settlement. This research aims for discovering the professional behaviour of health-care workes of Pelalawan community health center (Puskesmas), Pelalawan Regency that was assessed basing on the six elements of professional behaviour. The design of this reseacrh uses exploration method with qualitative approaches on nine health-care workers of Pelalawan community health center (Puskesmas), Pelalawan Regency, who selected by using snowball sampling method. Data collection was done by interview method and recorded with an audio recorder. The result of this research showed that all informants possess altruism, accountability, excellence, duty, honor and integrity and respect for other, and there are some informant who possess excellence. In general, half of the Pelalawan community health center (puskesmas) health-care workers possess the elements of professional behaviour in carrying their duty,especially in providing service the patients.Key word : professional behavior, health workers.